The role of Technology integration in Enhancing English language proficiency among Senior High School students - Nining Huriati; Hanna Maria Panggabean; Destri Wahyuningsih; Sherly Franchisca; Melda Agnes Manuhutu (Departement of Mathematics Education, 2024)
The integration of technology in English language instruction for senior high school students presents substantial benefits and challenges. This study explores how technology enhances engagement, provides access to authentic materials, supports personalized learning, and fosters collaboration. It also addresses the primary challenges, including the digital divide, insufficient teacher training, balancing digital and face-to-face interactions, digital literacy, resistance to change, and data privacy concerns. The findings suggest that while technology can significantly improve English language proficiency, a comprehensive approach is necessary to overcome the associated challenges and create an effective and inclusive educational environment.